1999
DOI: 10.1055/s-1999-2922
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Investigations of Analogues of the C15-C26 Phorboxazoles Segment

Abstract: A variety of analogues of phorboxazole C15-C26 segment have been prepared via three different reaction sequences. Structure activity investigations of the oxazole substitution pattern point to a pharmacophoric lead structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…While the anion of 21 added to aldehydes to form the anticipated adducts in modest yield, that of sulfone 22 failed to undergo the same reaction. This is in accord with the observations of Hoffmann . Fortunately, it transpired that the combination of TiCl 4 and Et 3 N promotes a smooth Knoevenagel-type condensation of 22 with aldehydes, leading to alkylidene derivatives in excellent yield, albeit as mixtures of geometric isomers.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…While the anion of 21 added to aldehydes to form the anticipated adducts in modest yield, that of sulfone 22 failed to undergo the same reaction. This is in accord with the observations of Hoffmann . Fortunately, it transpired that the combination of TiCl 4 and Et 3 N promotes a smooth Knoevenagel-type condensation of 22 with aldehydes, leading to alkylidene derivatives in excellent yield, albeit as mixtures of geometric isomers.…”
supporting
confidence: 87%
“…The exiguous volume of literature on the chemistry of 2-(sulfonyl)methyloxazole-4-carboxylates suggests that the anions of these species are exceedingly poor nucleophiles. To wit, the anion of 14 (Scheme ) fails to add to aldehydes, preventing the occurrence of Julia reactions. Once again, the peculiar behavior of these compounds is attributable to the effect of the 4-COOR functionality in that analogues lacking a 4-carbonyl group, e.g., 15 , do participate in Julia-type processes, though not very efficiently.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In accord with Hoffmann, , the anion of 71 , generated by deprotonation with NaH à la Fujita, failed to add to aldehydes. More significantly, even the presumably more reactive lithio derivative of 70 , prepared by deprotonation with LDA, added to aldehydes inefficiently, underscoring the unfavorable influence of the 4-COOR group.…”
Section: Resultsmentioning
confidence: 74%
“…While a limited volume of literature exists concerning the chemistry of 2-(sulfonyl)methyloxazole-4-carboxylates, the anions of these species are known to be poor nucleophiles. For instance, Hoffmann discovered that the metalated 64 (Scheme ) fails to add to aldehydes, , precluding the occurrence of Julia reactions. Once again, the COOMe substitutent must be responsible for such a behavior, for Williams demonstrated that sulfonyloxazoles lacking such a group, e.g., 65 , do undergo Julia−Kocienski reactions, albeit in only 45−50% yield …”
Section: Introductionmentioning
confidence: 99%